An Intricate Review on Nutritional and Analytical Profiling of Coconut, Flaxseed, Olive, and Sunflower Oil Blends - Roshina Rabail; Muhammad Asim Shabbir; Amna Sahar; Antoni Miecznikowski; Marek Kieliszek; Rana Muhammad Aadil (Molecules, 2021)
Vegetable oils (VOs), being our major dietary fat source, play a vital role in nourishment. Different VOs have highly contrasting fatty acid (FA) profiles and hence possess varying levels of health protectiveness. Consumption of a single VO cannot meet the recommended allowances of various FA either from saturated FA (SFA), monounsaturated FA (MUFA), polyunsaturated FA (PUFA), Ω-3 PUFAs, and medium-chain triglycerides (MCTs). Coconut oil (CO), flaxseed oil (FO), olive oil (OO), and sunflower oil (SFO) are among the top listed contrast VOs that are highly appreciated based on their rich contents of SFAs, Ω-3 PUFAs, MUFAs, and Ω-6 PUFA, respectively. Besides being protective against various disease biomarkers, these contrasting VOs are still inappropriate when consumed alone in 100% of daily fat recommendations. This review compiles the available data on blending of such contrasting VOs into single tailored blended oil (BO) with suitable FA composition to meet the recommended levels of SFA, MUFA, PUFA, MCTs, and Ω-3 to Ω-6 PUFA ratios which could ultimately serve as a cost-effective dietary intervention towards the health protectiveness and improvement of the whole population in general. The blending of any two or more VOs from CO, FO, OO, and SFO in the form of binary, ternary, or another type of blending was found to be very conclusive towards balancing FA composition; enhancing physiochemical and stability properties; and promising the therapeutic protectiveness of the resultant BOs.